Association between the FTO gene polymorphism and obesity in Brazilian adolescents from the Northeast region - Liliane dos Santos Rodrigues; Alcione Miranda dos Santos; Mayara Ingrid Sousa Lima; Vanda Maria Ferreira Simões; Silma Regina Pereira (Elsevier, 2020)
Objective: To investigate the association between the FTO gene polymorphism with obesity in Brazilian adolescents from the Northeast region. Method: This was a case-control study with adolescents aged 18 to 19 years. The case group consisted of 378 obese individuals and the control group of 378 non-obese individuals. Obesity was measured by percentage of body fat using the air displacement plethysmography technique. The study variables included data on socioeconomics, demographics, lifestyle, physical activity, waist circumference, waist-to-height ratio, and body mass index. To identify the rs9939609 polymorphism of the FTO gene, blood samples were obtained for genomic DNA extraction by the real-time PCR (Polymerase Chain Reaction) technique. Categorical variables were compared between the groups by the chi-squared test. The normality of the anthropometric measurements body mass index, waist circumference, waist-to-height ratio, and percentage of body fat was evaluated by the Shapiro-Wilk test. Comparison of the anthropometric measurements, stratified by the polymorphism genotypes, was performed by the Kruskal-Wallis test. The Hardy-Weinberg equilibrium was calculated. The significance level was set at 5%. Results: The variables gender, age, and physical activity showed significant differences between the groups (p < 0.001). The samples of obese and non-obese adolescents were in Hardy-Weinberg equilibrium (p = 0.0515). There was no significant difference between the genotypic (p = 0.719) and allelic frequencies (p = 0.812) regarding the case and control groups. When comparing the anthropometric measurements according to the genotypes (AA, AT, and TT), no significant difference was observed for body mass index (p = 0.337), waist circumference (p = 0.3473), percentage of body fat (p = 0.7096), and waist-to-height ratio (p = 0.2584). Conclusion: The excess adiposity of the study adolescents was not influenced by their genotype. Resumo: Objetivo: Investigar a relação do polimorfismo do gene FTO com obesidade em adolescentes no Nordeste brasileiro. Método: Estudo caso-controle realizado com adolescentes de 18 a 19 anos. O grupo caso foi formado por 378 indivíduos obesos e o controle por 378 não obesos. Obesidade foi medida pelo percentual de gordura corporal pela técnica de pletismografia por deslocamento de ar. Variáveis em estudo englobam dados socioeconômicos, demográficos, hábitos de vida, atividade física, circunferência da cintura, razão cintura-estatura e índice de massa corporal. Para identificação do polimorfismo rs9939609 do gene FTO foram obtidas amostras de sangue para extração do DNA genômico pela técnica de PCR em tempo real. Variáveis categóricas foram comparadas entre os grupos pelo teste qui-quadrado. Normalidade das medidas antropométricas índice de massa corporal, circunferência da cintura, razão cintura-estatura e percentual de gordura corporal foram avaliados pelo teste Shapiro-Wilk. Comparação das medidas antropométricas, estratificadas pelos genótipos do polimorfismo, foi realizada pelo teste Kruskall-Wallis. Calculou-se o equilíbrio de Hardy-Weinberg. Nível de significância adotado de 5%. Resultados: As variáveis sexo, idade e atividade física apresentaram diferenças significativas entre os grupos (p < 0,001). As amostras dos adolescentes obesos e não obesos estavam em equilíbrio de Hardy-Weinberg (p = 0,0515). Não houve diferença significante entre as frequências genotípicas (p = 0,719) e alélicas (p = 0,812) em relação aos grupos caso e controle. Quando comparadas as medidas antropométricas segundo os genótipos (AA, AT e TT), não foi observada diferença significante do índice de massa corporal (p = 0,3337), circunferência da cintura (p = 0,3473), percentual de gordura corporal (p = 0,7096) e razão cintura-estatura (p = 0,2584). Conclusão: O excesso de adiposidade dos adolescentes em estudo não foi influenciado pelo genótipo.